Study on repair control technology of soft surrounding rock roadway and its application. (October 2018) - Chen, Shunman; Wu, Aixiang; Wang, Yiming; Chen, Xun; Yan, Rongfu; Ma, Haoji
Abstract: In order to research the repair control technology of the inclined shaft with soft surrounding rock, the inclined shaft soft roadway of one phosphate mine in Hubei is taken as an example to study the damage characteristics, the deformation mechanism of the surrounding rock and repair control technology of it. The X-ray diffraction was employed to analyze the mineral components of the surrounding rock, also the surrounding rock contains clay minerals, which are easy to swell when in contact with water. The roadway mainly presents the damage characteristics of roof subsidence, two side walls extrusion, U-steel arch set bend or break, etc. The whole section double arch synergy reinforcement technology method of "sprayed concrete + grouting + anchor bolt + anchor cable" is proposed. And the technical parameters of the repair scheme are determined by theoretical analysis, engineering analogy and engineering practice. The numerical simulation is adopted to verify the feasibility of the whole section double arch synergy reinforcement scheme. The application results show that the large deformation roadway can be effectively controlled by the combined support scheme, which can provide certain references significance for similar engineering. Highlights: Roadways deformation with loose and fractured surrounding rock is large and difficult to control. The whole section double arch synergy reinforcement technology method was proposed. The mechanism of double arch synergy reinforcement technology was revealed. The new whole section double arch collaborative reinforcement technology was successfully experimented.